W krzywym zwierciadle: propagandowa funkcja biuletynów samorządowych - Adamczyk, Wojciech (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
The author points out the propagandist function as the main function of local self-government bulletins. These periodicals, published by local self-governments or their budgetary subordinates, frequently provide the main or even the only source of information about community matters, but they have transformed into a local elite’s propaganda tool. Con- sequently, this has led to an obvious limitation in two-way social communication in smaller administrative divisions and to the development of misinformation. As attention has become focused on propagandist activity, the principal objectives of a new social system and com- munication between the authorities and citizens that were set twenty years ago have been neglected. The paper also discusses the attempts at imposing legal limitations on local self-government publications and initiatives undertaken in this respect.
Propagandist Function in Local Self-Government Bulletins
Keywords: biuletyn samorządowy; funkcja propagandowa